System for psychophysical measurements of two-photon vision - Zielińska, Agnieszka; Kiluk, Karolina; Wojtkowski, Maciej; Komar, Katarzyna (Photonics Letters of Poland, 2019)
Two-photon absorption occurring in photoreceptors of human eye is responsible for perception of pulsed infrared laser beams. Color of perceived light corresponds to about half of wavelength of stimulating beam. This recently discovered phenomenon is called two-photon vision. However it is yet not clear how such phenomena could impact an ophthalmic diagnosis and therefore further studies are required. In this paper we present the system that enables future psychophysical experiments to extend knowledge about two-photon vision and its diagnostic value by identifying differences between two-photon and single-photon vision. Full Text: PDF References D. A. Atchison, G. Smith, Optics of the human eye (Butterworth-Heinemann 2000) CrossRef G. Palczewska et al. "Human infrared vision is triggered by two-photon chromophore isomerization", Proceedings of the National Academy of Sciences 111, 1428 (2014). CrossRef P. Artal, S. Manzanera, K. Komar, A. Gambín-Regadera, M. Wojtkowski, "Visual acuity in two-photon infrared vision", Optica 4, 1488 (2017). CrossRef K. Komar et al. "Posterior Eye Shape Measurement With Retinal OCT Compared to MRI", Investigative Ophthalmology & Visual Science 57, 196 (2016). CrossRef K. Komar et al. "Two-photon visual sensitivity of human cones - a psychophysical study", Investigative Ophthalmology & Visual Science 59, 4049 (2018). DirectLink S. A. Burns,R.H. Webb, Handbook of optics 28 (New York, McGraw Hill 1994) DirectLink R. W. Nygaard, T. E. Frumkes, "Calibration of the retinal illuminance provided by maxwellian views", Vision Research (1982) CrossRef P. Melillo et al. "Pupillometric analysis for assessment of gene therapy in Leber Congenital Amaurosis patients", Biomedical engineering online 11, 40 (2012) CrossRef P. A. Stanley, A. K. Davies, "The effect of field of view size on steady-state pupil diameter", Ophthalmic and Physiological Optics, 15, 601 (1995) CrossRef S. Mathôt, "Pupil mimicry is the result of brightness perception of the iris and pupil" Journal of Cognition 1 (2018) CrossRef M. M. Thomas, T. D. Lamb, "Light adaptation and dark adaptation of human rod photoreceptors measured from the a‐wave of the electroretinogram", The Journal of physiology 518, 479 (1999) CrossRef